2023
DOI: 10.35848/1347-4065/acbbd7
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of stereophonic projection lithography using parabolic mirror optics and collimated illumination from one side

Abstract: Capability of stereophonic projection lithography on arbitrarily but gently curved surfaces was demonstrated using plastic spoons as a reticle and specimens to be patterned. It had already been clarified that the patterned area size was drastically enlarged by illuminating the transparent reticle obliquely upward by collimated light from one side. Here, it was confirmed at first that 200 μm line-and-space patterns in 10 mm square area on a flat reticle were stably replicated on Si wafers with large exposure-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[36][37][38] As a result, patterns on curved reticles were successfully replicated on curved specimen surfaces. 39,40) However, the shapes of the replicated patterns on the curved specimens were slightly different from the original ones on the reticle. For this reason, pattern shape distortions caused by the parabolic mirror optics composed of a pair of paraboloids of revolution were investigated 41) using a flat reticle and wafers.…”
Section: Introductionmentioning
confidence: 95%
“…[36][37][38] As a result, patterns on curved reticles were successfully replicated on curved specimen surfaces. 39,40) However, the shapes of the replicated patterns on the curved specimens were slightly different from the original ones on the reticle. For this reason, pattern shape distortions caused by the parabolic mirror optics composed of a pair of paraboloids of revolution were investigated 41) using a flat reticle and wafers.…”
Section: Introductionmentioning
confidence: 95%
“…To realize the stereophonic projection lithography, characteristic optics composed of a pair of parabolic mirrors was applied [12][13][14][15][16] . And, owing to some distinguished ideas, it was demonstrated that patterns on curved reticles were successfully replicated on curved articles with the same shapes 17,18 . However, it was thought that reticles made by pasting transparent seals were insufficient for the practical use.…”
Section: Introductionmentioning
confidence: 99%